SOEP-Core - 2019: Sampling, nonresponse, and weighting in Sample P - Rainer Siegers; Hans Walter Steinhauer; Johannes König (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This paper provides details on the sampling design, fieldwork results, and nonresponse, as well as population adjustments for the 2019 Sample P of the Socio-Economic Panel (SOEP). Sample P adds the population of entrepreneurs and shareholders with high-value company shareholdings to the SOEP. Assuming that very wealthy individuals almost always invest a significant share of their wealth in company shares, this addition will significantly increase the number of cases and improve analysis potential of the SOEP for analyses focusing on the right tail of the wealth distribution. In order to identify members of our target population we used the global company database ORBIS which was provided by the business information publisher Bureau van Dijk (BvD). From those shareholders with residence in Germany representing the top percentile of the adult population of Germany in terms of their estimated value of shareholdings, we used a multistage stratified sampling design, and were ultimately able to conduct 1,960 interviews with households of this population. In order to correct for disproportionalities resulting from sampling design and attrition, we provide weighting factors that allow the analysis of the new cases both alone and in combination with the other SOEP samples.
Keywords: 330